Aktivitas Antioksidan Dan Organoleptik Kombucha Daun Kelor Dengan Lama Fermentasi Dan Konsentrasi Daun Kelor Yang Berbeda - WIDYASARI, Agustina, Dra. Aminah Asngad, M. Si (2016)
Kombucha is a beverage prod microbial starter kombucha is name Acetobacter xylinum and yeast. In generally, kombucha made by using tealeaves, that has high antioxidant content. One of leaf that has high antioxidant content expect tealeaves is moringa leaves. The purpose of this research is to know the activity of the antioxidant of moringa leaves kombucha and organoleptik moringa leaves kombucha. This method that used in this research is completely randomized design with 2 factors, the first factor are the concentration of dry moringa leaves 10 g (R1), 20 g (R2), 30 g (R3), the second factor are the long fermentation 4 day (F1), 8 day (F2), 12 day (F3). The result of the research is showing the higher antioxidant activity is R3F2 (30 g moringa leaves and 8 day fermentation) amounted to 67,59% and the lower antioxidant activity is R1F3 (10 g moringa leaves and 4 day fermentation) amount to 23,83%. The quality of organoleptik moringa leaf kombucha with the higher received is R2F1 that has brown color, the aroma has a little aroma like kombucha and a little sour taste. The conclusion of this research is long fermentation and concentration of moringa leaves influence on the antioxidant activity and organoleptik kombucha.